Policy Intervention in Debt Renegotiation: Evidence from the Home Affordable Modification Program - Agarwal, Sumit; Amromin, Gene; Ben-David, Itzhak; Chomsisengphet, Souphala; Piskorski, Tomasz; Seru, Amit (Journal of Political Economy, 2017)
We evaluate the effects of the 2009 Home Affordable Modification Program (HAMP) that provided intermediaries with sizable financial incentives to renegotiate mortgages. HAMP increased intensity of renegotiations and prevented a substantial number of foreclosures but reached just one-third of its targeted indebted households. This shortfall was in large part due to low renegotiation intensity of a few large intermediaries and was driven by intermediary-specific factors. Exploiting regional variation in the intensity of program implementation by intermediaries suggests that the program was associated with a lower rate of foreclosures, consumer debt delinquencies, house price declines, and an increase in durable spending.